2007
DOI: 10.1897/07-137r.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity and genotoxicity assessment of cytostatic pharmaceuticals

Abstract: The fate and effects of cytostatic (anticancer or antineoplastic) pharmaceuticals in the environment are largely unknown, but they can contaminate wastewater treatment effluents and consequently aquatic ecosystems. In this paper, we have focused on five cytostatic compounds used in high amounts (cyclophosphamide, cisplatin, 5-fluorouracil, doxorubicin, and etoposide), and we have investigated their ecotoxicity in bacterial Pseudomonas putida growth-inhibition test, algal Pseudokirchneriella subcapitata growth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(31 citation statements)
references
References 26 publications
2
28
1
Order By: Relevance
“…1A, B and SM-3). The observed results for CP on P. subcapitata (SM-3) are in the agreement with literature (Grung et al, 2008;Zounkova et al, 2007), whereas to our knowledge the effects of IF towards these species are yet to be reported. Since prokaryotic organisms (cyanobacteria belongs to prokaryotes) are more abundant in biological water treatment than eukaryotic organisms (Wagner and Loy, 2002) and because the alga and cyanobacteria did not differ in the susceptibility towards exposure to CP and IF, all following experiments involving metabolites/TPs, mixtures of compounds and toxicity of the CP and IF after UV irradiation were performed using only S. leopoliensis.…”
Section: Individual Compoundssupporting
confidence: 91%
See 1 more Smart Citation
“…1A, B and SM-3). The observed results for CP on P. subcapitata (SM-3) are in the agreement with literature (Grung et al, 2008;Zounkova et al, 2007), whereas to our knowledge the effects of IF towards these species are yet to be reported. Since prokaryotic organisms (cyanobacteria belongs to prokaryotes) are more abundant in biological water treatment than eukaryotic organisms (Wagner and Loy, 2002) and because the alga and cyanobacteria did not differ in the susceptibility towards exposure to CP and IF, all following experiments involving metabolites/TPs, mixtures of compounds and toxicity of the CP and IF after UV irradiation were performed using only S. leopoliensis.…”
Section: Individual Compoundssupporting
confidence: 91%
“…Freshwater Alga and Cyanobacteria, Growth Inhibition Test) are commonly performed (OECD TG 201, 2011). A literature overview revealed that only two CP growth inhibition studies have been performed using the alga Pseudokirchneriella subcapitata, both showing low toxicity with no observed effect concentration (NOEC) > 100 mg L À1 (Grung et al, 2008;Zounkova et al, 2007). No published ecotoxicity studies, to the authors knowledge, have included IF and the human metabolites/TPs of CP and IF.…”
Section: Introductionmentioning
confidence: 99%
“…As one can see in Tables 5, 3 positive alerts from the different models of the ICH M7 guideline conformal set from CASE Ultra indicate possible mutagenic and genotoxic activities of 5-FU in the Ames test with different strains of Salmonella and E. coli. These results are in line with previous in vivo studies which have already reported the potential mutagenic and genotoxic effects of 5-FU (Zounkova et al (2007); Yasunaga et al (2006)). …”
Section: Identification and Kinetics Of Transformation Productssupporting
confidence: 93%
“…Zounkova et al (2007) performed genotoxicity assays with 5 cytotoxic compounds using Escherichia coli SOS chromotest (with and without the use of metabolic activator) and Saccharomyces cerevisiae (eukaryotic yeast GreenScreen Assay (GSA)). The results indicated 5-FU as the most genotoxic compound for S. cerevisiae (Minimal Genotoxic Concentration -MGC = 0.02 mg/L) and very toxic in the assays involving E. coli without metabolic activation (MGC = 1.4 mg/L).…”
Section: Compoundmentioning
confidence: 99%